Evaluación del método flexitest en los niños y niñas de la escuela de ciclismo de Cajicá - categoría pre infantil e infantil (2015)
Recent work conducted at the Institute of Sports and Recreation Cajicá, to intervene in the sports training of children of school road cycling training. The methodology used was the collection of photographic records that gathers information about the flexibility of each athlete, in order to assess the range of motion of the joints of the body, and likewise, analyze what state through Flexitest method.